Evaluating the Effect a of Handout on Community Pharmacists' Opioid Safety Counseling - Tanvee Thakur; Betty Chewning (MDPI AG, 2021)
Community pharmacists are the most accessible healthcare professionals to counsel patients about opioid risks and safety. Resources such as handouts are needed to improve pharmacists' self-efficacy about opioid safety counseling. This study aims to understand the effects and usefulness of handouts in opioid risk and safety counseling in community pharmacists. Three community pharmacies participated in this study for three weeks, where five pharmacists participated in completing a survey about the process and integration of a handout in opioid medication consultation. Pharmacists filled the survey after counseling patients for opioid medication/s. Field observations were conducted at one of these sites as well. A total of 57 consults were recorded via surveys in these pharmacies. Only using the handout to guide the conversation was rated much less useful than integrating the handout and showing it to patient in the consult (β = 0.94, adjusted R2 = 0.29, p < 0.00001). Satisfaction about the patient education provided increased if opioid risks and safety topics were discussed (β = 0.7, adjusted R2 = 0.32, p = 0.00015). Patients seemed engaged in the consults, which was evident from the head nods, questions asked, and attention toward the pharmacist. Effective communication with patients or patient caregivers about opioid safety can be accomplished by using and modeling use of this handout and by providing structured instructions to use this handout optimally.